2015
DOI: 10.3923/jfrs.2015.62.72
|View full text |Cite
|
Sign up to set email alerts
|

Production and Quality Evaluation of Green and Black Herbal Teas from Moringa oleifera Leaf

Abstract: Freshly plucked Moringa oleifera leaves were processed into green and black herbal teas, due to its nutritional, pharmacological and medicinal properties. The unit operations were plucking, destalking and steaming for green tea or withering, grinding, fermentation for black tea prior to drying, milling, grading and packing. The tea samples were subjected to chemical and microbial load analyses, using standard methods. The results revealed the following ranges: proximate parameters; crude protein (7.25-26.62%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Tea with high moisture content has a reduced shelf life and thus promotes the growth of harmful microorganism. Although honeybush tea had a higher moisture content, the value was lower than the reported values of powdered moringa oleifera leaves (8.76%), moringa black tea (12.62%) and moringa green tea (10.37%) (Okafor and Ogbobe, 2015). Similar to this study, Adnan et al (2013) observed a moisture range of 2.46–7.46% for green and black tea.…”
Section: Resultsmentioning
confidence: 61%
“…Tea with high moisture content has a reduced shelf life and thus promotes the growth of harmful microorganism. Although honeybush tea had a higher moisture content, the value was lower than the reported values of powdered moringa oleifera leaves (8.76%), moringa black tea (12.62%) and moringa green tea (10.37%) (Okafor and Ogbobe, 2015). Similar to this study, Adnan et al (2013) observed a moisture range of 2.46–7.46% for green and black tea.…”
Section: Resultsmentioning
confidence: 61%
“…Teh dapat dijadikan bahan dasar inovasi pengembangan produk minuman fungsional salah satunya untuk diabetes. Penelitian terdahulu telah melaporkan tentang kombinasi minuman teh dengan beberapa bahan dari tumbuhan yang berbeda juga bagian tumbuhan yang berbeda seperti biji, bunga, buah, daun, dan batang bertujuan untuk meningkatkan nilai nutrisi dan nilai farmakologisnya (Namdev & Gupta, (2015); D'Ulivo (2018); Ochanda et al, (2015); Gulua et al, (2018)) atau membuat teh hijau atau teh hitam dari bahan lain seperti teh daun kelor, Withania somnifera, dan rosella (Oduro et al, (2013); Onyekwelu, C. N., Oragba, (2019); Okafor & Ogbobe, (2015); Namdev & Gupta, (2015). Kandungan senyawa polifenol pada teh merupakan suatu kelebihan tersendiri karena perannya sebagai penghambat reaksi oksidasi dan menangkap radikal bebas.…”
Section: Hasil Dan Pembahasanunclassified